Neural interfaces based on amorphous silicon carbide ultramicroelectrode arrays. Issue 3 (22nd November 2018) - Deku, Felix; Ghazavi, Atefeh; Cogan, Stuart F
Size and material considerations are important in the development of next-generation chronically reliable neural interface devices. In this review, we discuss the use of amorphous silicon carbide (a-SiC) for the fabrication of indwelling electrode arrays with ultrathin penetrating shanks for neural stimulation and recording. The a-SiC film is stable in saline environments and has a high intrinsic stiffness that allows fabrication of tissue-penetrating arrays with extremely small cross-sectional areas (<60 μm 2 ). Present literature on arrays with extremely small shanks and/or ultramicroelectrode (UME) sites are reviewed. Properties of a-SiC films and their current biomedical applications are summarized. Reduced shank dimensions increase the flexibility of high Young's modulus a-SiC arrays. Iridium oxide-coated UMEs had electrochemical properties suitable for neural recording and stimulation, and recorded neural signals with high amplitudes and high signal-to-noise ratios. UMEs and a-SiC may provide a platform for next-generation high-density chronic neural interface devices.